Epidemiology of pediatric uveitis and associated systemic diseases - Yoonkyeom Shin; Ji-Man Kang; Junwon Lee; Christopher Seungkyu Lee; Sung Chul Lee; Jong Gyun Ahn (BMC, 2021)
Abstract Background The early detection of uveitis associated with systemic inflammatory disease in children is important for proper treatment and prognosis. However, the diagnosis may be delayed because of difficulties in childhood examinations and early minor systemic symptoms. The objective of our study was to identify the pattern of childhood uveitis and investigate the frequency and clinical features of rheumatic diseases in pediatric patients with uveitis. Methods This retrospective observational study reviewed the medical records of children (age ≤ 18 years) with uveitis at a Korean tertiary hospital between January 2005 and December 2018. Data collected included the age at onset of uveitis, sex, anatomic location of ocular inflammation, comorbid disease (including systemic inflammatory disease), ocular complications, relevant laboratory data, and treatment. Fisher's exact test was used to compare categorical variables and the Mann-Whitney U test was used to compare continuous variables. A p-value of < 0.05 was considered statistically significant. Results A total of 155 pediatric patients with uveitis were included in this study. The median age at diagnosis was 13.0 years (interquartile range, 9.5-16.0 years). The male-to-female ratio was 1.09. The process was unilateral in 51.6% of children. Anterior uveitis, panuveitis, intermediate uveitis, and posterior uveitis represented 51.6, 26.5, 6.5, and 1.9% of the cases, respectively. Idiopathic uveitis (65.2%) was the most frequent type of uveitis. Systemic rheumatic disease associations were responsible for 28.4% of the cases, among which juvenile idiopathic arthritis (JIA) was the most frequent cause (14.8%). Human leukocyte antigen (HLA)-B27 and antinuclear antibody (ANA) positive rates were significantly higher in patients with JIA than in those with idiopathic uveitis (p = 0.006 and p = 0.007, respectively). Conclusions Approximately one-third of children with uveitis in Korea have a systemic rheumatic disease, of which JIA accounts for the majority of cases. HLA-B27 and ANA can serve as risk factors for JIA-associated uveitis.